2003
DOI: 10.1001/archopht.121.8.1141
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Error and Ethnicity in Children

Abstract: of refractive error and ocular development in children from 4 ethnic groups. Patients and Methods: The study population included 2523 children (534 African American, 491 Asian, 463 Hispanic, and 1035 white) in grades 1 to 8 (age, 5-17 years). Myopia was defined as −0.75 diopters (D) or more and hyperopia as +1.25 D or more in each principal meridian, and astigmatism was defined as at least a 1.00-D difference between the 2 principal meridians (cycloplegic autorefraction). Results: Overall, 9.2% of the children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
239
9
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(270 citation statements)
references
References 15 publications
13
239
9
9
Order By: Relevance
“…The distributions of refractive frequency in various age groups displayed a clear change, the prevalence of hyperopia significantly decreased and the prevalence of myopia increased (10). It has been reported a prevalence of myopia of 11.6% for children aged 5 to 17 years and 20% for children aged 12 years and increased to 33% for those aged ≥ 20 years (46)(47)(48), and in study on 2353 Austeralian students aged 11-15-years old, the prevalence of myopia was 4.6% and this amount was 6.1% among European Caucasian and Middle Eastern children respectively, whereas prevalence of myopia was 31.5% among South Asian children (49). Similar to our findings, the increasing prevalence of myopia with age was observed in the population-based studies in some countries such as Taiwan (5), Australia (6), Singapore (7), Malaysia (13), and Indonesia (50).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The distributions of refractive frequency in various age groups displayed a clear change, the prevalence of hyperopia significantly decreased and the prevalence of myopia increased (10). It has been reported a prevalence of myopia of 11.6% for children aged 5 to 17 years and 20% for children aged 12 years and increased to 33% for those aged ≥ 20 years (46)(47)(48), and in study on 2353 Austeralian students aged 11-15-years old, the prevalence of myopia was 4.6% and this amount was 6.1% among European Caucasian and Middle Eastern children respectively, whereas prevalence of myopia was 31.5% among South Asian children (49). Similar to our findings, the increasing prevalence of myopia with age was observed in the population-based studies in some countries such as Taiwan (5), Australia (6), Singapore (7), Malaysia (13), and Indonesia (50).…”
Section: Discussionmentioning
confidence: 97%
“…Uncorrected refractive errors are the potential causes of learning difficulties and may limit the choices children make in their daily activities. New policies are needed to be developed to address this public health problem (46). Suggesting that we should develop preventive strategies and also develop approaches towards early treatments of these sorts of visual disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…In a large study of the refractive error of American children, Kleinstein and colleagues 62 noted an increased prevalence of astigmatism in children of Asian and Hispanic origin. Asian children displayed a prevalence of astigmatism of one or more dioptres of 33.6 per cent and Hispanic children a prevalence of 36.9 per cent.…”
Section: Astigmatism In Ethnic Groupsmentioning
confidence: 99%
“…Several studies have shown associations between "presumed" eyelid pressure and changes in corneal topography, particularly induced astigmatism. [29][30][31][32][33][34] There are conflicting results regarding whether Asian palpebral aperture size (PAS) is smaller than that of non-Asians. 5 The reasons responsible for these discrepancies include different sampling of study cohorts, definitions of ethnic groups, and measurement techniques.…”
Section: Eyelidmentioning
confidence: 99%